National and Local Trends in Serious Violence, Firearm Victimization, and Homicide. Issue 3 (August 2019) - Lauritsen, Janet L.; Lentz, Theodore S.
The recent upturn in U.S. homicide rates may have resulted from increases in the number of serious violent incidents, growth in the percentage involving firearms, or increases in lethality. Data from the National Crime Victimization Survey (NCVS) and Supplementary Homicide Reports (SHR) suggest that the national homicide increase was not driven by increases in serious violence or the proportion of these crimes involving firearms, but may be related to a longer-term increase in lethality. In St. Louis, the increase was concentrated in communities that previously had the highest violence rates, but changes in the structural conditions and population composition were unrelated to the upsurge in homicide.